2016
DOI: 10.3389/fimmu.2016.00652
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferons in Bacterial Infections: A Balancing Act

Abstract: Defense against bacterial infections requires activation of the immune response as well as timely reestablishment of tissue and immune homeostasis. Instauration of homeostasis is critical for tissue regeneration, wound healing, and host recovery. Recent studies revealed that severe infectious diseases frequently result from failures in homeostatic processes rather than from inefficient pathogen eradication. Type I interferons (IFN) appear to play a key role in such processes. Remarkably, the involvement of typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 78 publications
1
89
0
2
Order By: Relevance
“…Inhibition of immune responses by type I IFNs has been shown to be deleterious during infection with the facultative intracellular Gram‐negative bacterium Francisella novicida . Moreover, IFNβ exacerbates infection with Salmonella typhimurium by reducing the ability of the host to launch a complete immune response . These studies highlight the importance of tightly regulating IFNβ production in response to Gram‐negative bacteria in order to avoid detrimental excessive inflammation and associated pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of immune responses by type I IFNs has been shown to be deleterious during infection with the facultative intracellular Gram‐negative bacterium Francisella novicida . Moreover, IFNβ exacerbates infection with Salmonella typhimurium by reducing the ability of the host to launch a complete immune response . These studies highlight the importance of tightly regulating IFNβ production in response to Gram‐negative bacteria in order to avoid detrimental excessive inflammation and associated pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Although a virtually universal antiviral immune signal, the consequences of IFN-I signaling on bacterial pathogens has remained less clear and is in many cases detrimental to the host (Kovarik et al, 2016). Several intracellular bacterial pathogens, including Listeria monocytogenes, Mycobacterium tuberculosis and Stm, appear to have decreased virulence in IFNAR1-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the large size of the “interferome” and the complex interactions of ISGs with thousands of additional cellular proteins (Hubel et al, 2019), knowledge of the full spectrum of IFN-I-mediated changes in cellular function is incomplete. Although IFN-Is are known to have critical roles in antiviral responses, their functions in bacterial infection are less clear, and IFN-I signaling has been reported to be either protective or detrimental to the host depending on the specific bacterial pathogen (Kovarik et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We found that TET2 regulates primarily genes involved in the innate immune response and more specifically genes related to the TLR induced-Type I IFN response (e.g., Stat1, Stat3, Irf1, Irf7) (Noppert et al, 2007) (Luu et al, 2014). Traditionally, Type I IFN response was considered solely for defense against viral and bacterial infections (Stifter and Feng, 2015) (Kovarik et al, 2016). However, in the brain, and under sterile inflammatory conditions, there are increasing numbers of reports showing activation of the Type I IFN response in ischemia (McDonough et al, 2017), spinal cord injury (Impellizzeri et al, 2015) and in two different AD mouse models, the 5xFAD (Landel et al, 2014) and APP/PS1 (Taylor et al, 2014), as well as in AD patients (Taylor et al, 2014).…”
Section: Discussionmentioning
confidence: 95%